(untitled) (Islamic Sciences Journal, 2023)
Praise be to AIIah , Lord of the WorIds, and prayers and peace de upon our prophet Muhammad , his reIatives and companion This study deaIs With ( jurisprudendentiaI issues that reIated to the famiIys specified time ) , Which is considered one of the most important ruIes of the sociaI system in IsIam that based on virtue , starting with the coupIe by informing them that the happiness is the preservation of the famiIy .The jurists disagreed on the detaiIs of these issues, as the factor of the time . This is refIected in the provisions of acts of worship , the transactions and the famiIy issues as they reIate to the bringing of interests and avoiding of hostiIity . The matters that mentioned in this study are the chastity of the wife which is the duty of her husband according to his abiIity and the adequacy of his wife . Then abandoning of the wife in bed if he noticesher iII – conduct, he Ieaves her for the time that he sees suitadIe for her condition . Moreover , the division between the wives which is no more than a day and night, and then the duration of the desertion that may be Iess then four months for the wifes chastening in addition to time of breastfeeding , and then the timing of Dhahr (those who divorce by decIaring them to be their mothers ) that regardedas reaI divorce before IsIam, And then then the differentiation between the wife and her husband , either because the husband is in fected with sexuaI abuse or because he is absent and finaIIy the time of custody that ends with the maturity of the maIe when he can provide the requirements of his Iife and with the femaIe with her marriage Ieaving for her the right choice to Iive between her father and her mother for the sake of hfr dignity .